Distal Biceps Tendon Anatomic Repair. Issue 4 (October 2017) - Schmidt, Christopher C.; Styron, Joseph F.; Lin, Edward A.; Brown, Brandon T.
Abstract : Distal biceps injuries, which usually occur in active middle-aged men, can result in chronic pain and loss of supination and flexion strength3, 4 . Surgical repair of a ruptured distal biceps tendon can reliably decrease pain and improve strength compared with nonoperative management3, 4 . However, even following successful healing and rehabilitation of a surgically repaired biceps tendon, full supination strength is rarely restored5 -7 . The expected outcome following distal biceps repair using a traditional anterior approach is a measurable loss of rotational strength, especially from neutral to supinated positions5, 7 . This deficit can lead to difficulty with occupational and recreational activities5, 8 . The center of an uninjured biceps tendon inserts into the radial tuberosity 6.7 mm anterior to its apex9, 10 . This posterior location forces the biceps tendon to wrap around the radial protuberance during pronation, thus utilizing the protuberance as a mechanical cam during forceful forearm supination10, 11 . The distal biceps tendon comprises a medial short head and lateral long head; the 2 heads are continuations of the proximal muscles2, 20, 21 . The short head inserts distal to the long head on their radial attachment site2, 20, 21 . Performing a distal biceps repair via an anterior approach typically places the center of the reattachment site 12.9 mm anterior to its apex or approximately 6 mm anterior to an uninjured control tendon9 . This shifts the repair site from its anatomic location (posterior to the radial protuberance) to a new nonanatomic location (on top of the protuberance). This anterior reattachment location decreases the cam effect of the radial protuberance, resulting in an average supination loss of 10% in neutral rotation and 33% in 60° of supination7, 10 . A posterior approach to the radial tuberosity using 2 separate intramedullary buttons for the short and long heads reliably positions the distal biceps insertion at its anatomic footprint, which is posterior to the radial protuberance9, 10, 11 . This technique has been named the distal biceps tendon anatomic repair . Not only does it restore the normal supination cam effect of the radial protuberance, but it also provides superior initial fixation strength, with load to failure strength similar to the native tendon1 . The distal biceps anatomic repair can be divided into the following 9 key steps: Step 1: Preoperative planning; Step 2: Positioning; Step 3: Identifying and retrieving the tendon; Step 4: Preparing the 2 heads of the tendon; Step 5: Posterior exposure of tendon footprint; Step 6: Drilling the short and long-head drill holes; Step 7: Passage of the tendon; Step 8: Unicortical button fixation; Step 9: Alternative fixation: cortical trough; and Step 10: Postoperative management.